REFLECTIVE APPROACH TO THE FORMATION OF THE EDUCATIONAL AND INFORMATION ENVIRONMENT OF THE DISTANCE EDUCATION SYSTEM IN HIGHER TECHNICAL EDUCATION INSTITUTIONS: activity-performance paradigm; cognitive-reflexive approach; educational and information environment; educational system; multimedia educational and methodical complex (MEMC); personal and professional development of a specialist; system-planetary thinking; the trajectory of learning success - Luzik, Elvira; Semychenko, Valentyna; Ladohubets, Nataliia; Mykheieva, Tamara (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2022)
The research is devoted to substantiation of theoretical and methodical bases of designing of multimedia educational and methodical complex (MEMC) for distance learning in the appropriate educational and information environment and experimental check of efficiency of its use in institution educational process of higher technical education. Research methods. The pedagogical experiment of the study included three stages. At the ascertaining stage for substantiation of use expediency of educational and information technologies scientific methods were used: structural-scientific, system-functional analysis; empirical methods: diagnostics, observation, questionnaires, surveys; methods (R. Kettell, K. Rogers, T. Ilyina, L. Kabardova, A. Lachins, S. Budassi, M. Ostasheva) and test tasks for input and output control. Results. During the ascertaining stage of the research to identify the quality and efficiency of the distance learning process, a survey was conducted among foreign (86 students from 28 countries) and Ukrainian NAU students, the results are presented in Table 1. In the formative experiment the general population was: 18 students (experimental group) and 20 students (control group). The results of the formative experiment showed the positive dynamics of changes in the indicators of the motivational and value component of the formation of future practical psychologists readiness to use educational and information technologies in the distance learning process. The obtained results confirmed the hypothesis that the MEMC using in the educational process of HTEI contributes to: the creation of an interactive educational environment for an effective learning process based on the competence-reflexive approach; ensuring educational interaction between participants in the educational process; availability of conditions for self-control, taking into account rigid and flexible feedback. Conclusions. MEMC for distance learning includes basic, advanced and proficiency training courses and consists of the following elements: theoretical and methodological unit, training modules, control section. The system-engineering part of learning success has become a system-forming competence-target element of MEMC as an updated base of newly formed and accumulated knowledge, where educational interaction is realized both between professor and students and with other sources of educational and applied information